Management of purple blotch (Alternaria porri) of garlic (Allium sativum) with fungicides - Sugha, S K (The Indian Journal of Agricultural Sciences, 2012)
A field trial was conducted during winter season of 1989-90, 1990-91 and 1991-92 on the management of purple blotch [Alternaria porri (Ellis) Cif.] of garlic (Allium satlvum L.). Clove dip in 0.25% solution of iprodione, thiram and triadimenol for 1 hr before sowing provided very good protection from the disease up to 120 days after sowing. Three foliar sprays of iprodione @ 0.1 % alone or in combination with copper oxychloride 0.1 % and mancozeb 0.1% at 15-day intervals resulted in 53.5 to 62% protection to the crop. Clove dip iprodione 0.25% for 1 hr before sowing followed by 2 sprays of metalaxyl + mancozeb (Ridomil MZ @ 0.25%) or iprodione @ 0.2% proved highly effective, giving 79.6-84.9% control of the disease. Iprodione and metalaxyl + mancozeb were superior to chlorothalonil, copper oxychloride, mancozeb and zineb in providing protection to garlic crop from purple blotch in Himachal Pradesh.